Synthesis and characterization of adsorbents for the elimination of nitrates and bromates from water aiming to develop a continuous oxyanion water elimination system - Azaro, Macarena Soledad (2021)
It is known that the excess of oxyanions such as NO⁻₃ and BrO⁻₃ in drinking water affects its quality. In this work, three adsorbents (montmorillonite (Mt), silica (Si), and diatomaceous earth) loaded with hexadecyl- (H) and octadecyl-trimethylammonium (O) were used to remove these oxyanions from aqueous solutions by adsorption. In batch systems, the highest NO⁻₃ removal was obtained with Mt modified with H and O (Mt-H and Mt-O), attaining 33% and 50%, respectively, while for BrO⁻₃ removal Si modified with H and O, Si-H and Si-O samples, reached 38% and 42%, respectively. A direct relationship between the adsorption capacity of NO⁻₃ and BrO⁻₃ and the mass of the adsorbent was found in column filtration tests with Mt-O and Mt-H samples in standard solution and real groundwater samples. The adsorption capacity of the column, in the groundwater sample, remained constant after two reuses.The results obtained are promising for the development of a continuous oxyanion removal system containing the low-cost clay Mt modified with either H or O.